The Newport eye: design and initial evaluation of a novel foreign body training phantom. Issue 4 (25th April 2013) - Marson, Ben A; Sutton, Lynne J
Abstract : To improve SHO confidence in corneal foreign body removal, a novel training phantom is proposed. This phantom is a polyvinyl and gelatine-based model, easily fabricated in the emergency department (ED). Use of the phantom results in a significant improvement in SHO confidence, and therefore, makes a useful, cost-effective adjunct for ED training.